Нарушения электролитного обмена в тканях крыс при дегидратации и гипергидратации - Дергунов, А.В.; Хмара, В.М.; Гусев, Г.П. (Актуальні проблеми транспортної медицини, 2012)
Диагностика нарушений гомеостаза воды и электролитов в организме человека и их коррекция были проведены в эксперименте на животных. Исследовалось содержание воды, натрия и калия в сыворотке крови и тканях у крыс в условиях дегидратации и гипергидратации. Опыты выполнялись на животных массой 250-300 гр. По результатам эксперимента можно прийти к выводу, что концентрация белка в плазме крови (но не гематокрит) является показателем сгущения или разбавления крови, и отражает состояние водного баланса организма. Наиболее адекватным показателем нарушения водно-электролитного баланса организма могут служить изменения состава скелетной мышцы. При этом водноэлектролитный состав тканей головного мозга, несмотря на выраженные нарушения водного баланса организма, остаётся неизменным. Отёк мозга в эксперименте обычно вызывается травмой, ишемией или токсинами. Діагностика порушень гомеостазу води і електролітів в організмі людини та їх корекція були проведені в експерименті на тваринах. Досліджувався вміст води, натрію і калію в сироватці крові і тканинах у щурів в умовах дегідратації та гіпергідратації. Досліди виконувалися на тварин масою 250-300 гр. За результатами експерименту можна прийти до висновку, що концент-рація білка в плазмі крові (але не гематокрит) є показником згущення або розведення крові, і відображає стан водного балансу організму. Най-більш адекватним показником порушення водно-електролітного балансу орга-низма можуть служити зміни складу скелетної м’яза. При цьому водно-електролітний склад тканин головного мозку, незважаючи на виражені нару-ня водного балансу організму, залишається незмінним. Набряк мозку в експе-рименте зазвичай викликається травмою, ішемією або токсинами. Diagnostics of water-electrolyte imbalance in the human body as well as correction of this disorder are of significant interest for clinical practice in light of the use of infusion therapy. Such data can be acquired mainly through experiments on animals. Water, sodiumand potassium levels in the blood of the heart-, skeletal muscle-, lung-, liver-, brain tissues were studied in dehydrated and hyperhydrated rats. Blood protein concentration increased during dehydration (DH) and reduced during hyperhydration. The obtained data suggest that blood protein (rather that hematocrit) should be the index of blood thickening or dilution of the blood, reflecting the state of water balance in the body. Of all tested tissues it is changes in composition of the skeletal muscle that can be the most demonstrative indicator of water-electrolyte imbalance. Since this tissue represents a considerable portion of the total body mass, the skeletal muscle is considered to be the main source of water in case of both DH and intracellular hyperhydration. Again, fluid and electrolyte metabolism of the brain remains the same in spite of pronounced water imbalance in the body. A number of authors have reported changes in the amount of water in the brain of animals to be much less significant compared to those in the skeletal muscle and other organs in case of both DH and hyperhydration. Therefore, in experiments cerebral edema is usually caused by injuries, ischemia or toxins.